2001
DOI: 10.1136/jcp.54.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of alpha-catenin, beta-catenin, and gamma-catenin is associated with high cell proliferative activity and poor differentiation in non-small cell lung cancer

Abstract: Aims-To investigate the expression of catenins ( , , and ) in non-small cell lung carcinoma (NSCLC) and its relation to clinicopathological factors and prognosis. Methods-The expression of catenins was analysed immunohistochemically in 261 patients with resected NSCLC, diagnosed between 1978 and 1996 in eastern Finland. The cell proliferation index of the tumours was analysed by means of an image analyser. The staining results were compared with clinicopathological characteristics and survival. Results-Normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 30 publications
7
62
1
Order By: Relevance
“…Some authors, in agreement with the present observations, reported restricted cytoplasmic localization and never found b-catenin nuclear translocation, 34,[42][43][44][45] whereas some other studies show cytoplasmic and nuclear localization of b-catenin. 33,46-48 Although we did not detect b-catenin in the nucleus, we cannot rule out the possibility that b-catenin accumulation in the cytoplasm could lead to the translocation of undetectable levels of the protein to the nucleus, which could lead to the activation of target genes. Several mechanisms have been reported to contribute to the dowregulation of key adhesion proteins.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some authors, in agreement with the present observations, reported restricted cytoplasmic localization and never found b-catenin nuclear translocation, 34,[42][43][44][45] whereas some other studies show cytoplasmic and nuclear localization of b-catenin. 33,46-48 Although we did not detect b-catenin in the nucleus, we cannot rule out the possibility that b-catenin accumulation in the cytoplasm could lead to the translocation of undetectable levels of the protein to the nucleus, which could lead to the activation of target genes. Several mechanisms have been reported to contribute to the dowregulation of key adhesion proteins.…”
Section: Discussionmentioning
confidence: 90%
“…In human carcinogenesis, only fully established lung carcinomas have been studied for E-cadherin/catenin complex alterations. 4,[33][34][35] In the present model, we have been able to study these molecules in early hyperplastic and preneoplastic lesions of bronchiolar and alveolar type II cells. We observed that a-and b-catenin appeared in a granular cytoplasmic pattern in tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Retera and associates investigated 101 cases of non-small cell lung cancers and noted an association of reduced expression of ␤-catenin with an unfavorable prognosis, but they did not refer to aberrant nuclear localization of ␤-catenin (21). Pirinen and associ- ates recently reported nuclear/cytoplasmic expression for ␤-catenin in only 16 (7%) of 261 non-small cell lung cancers (22). Sunaga and associates studied 46 cultured cell lines of lung cancer as well as 47 resected lung cancer specimens and found mutations in exon 3 of the ␤-catenin gene in only 1 (2%) of the 46 cell lines and 2 (4%) of the 47 lung tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Normal positive β-catenin expression was located on the cell membrane, and distributed along the cell membrane continuity as small brown granules. The criteria were according to Pirinen (Pirinen et al, 2001). A total of 10 high magnification fields were randomly selected from each section, and 100 tumour cells were counted from every field.…”
Section: Immunochemistrymentioning
confidence: 99%